Targeting lysosome function causes selective cytotoxicity in VHL-inactivated renal cell carcinomas. (26th September 2019) - Bouhamdani, Nadia; Comeau, Dominique; Coholan, Alexandre; Cormier, Kevin; Turcotte, Sandra
Abstract: The inactivation of the tumor suppressor gene, von Hippel-Lindau (VHL), has been identified as the earliest event in renal cell carcinoma (RCC) development. The loss of heterogeneity by chromosome 3p deletion followed by inactivating mutations on the second VHL copy are events present in close to 90% of patients. Our study illustrates a lysosomal vulnerability in VHL-inactivated RCC in vitro . By investigating the mechanism of action of the previously identified STF-62247, a small bioactive compound known for its selective cytotoxic properties towards VHL-defective models, we present the promising approach of targeting truncal-driven VHL inactivation through lysosome disruption. Furthermore, by analyzing the open platform for exploring cancer genomic data (cbioportal), we uncover the high alteration frequency of essential lysosomal and autophagic genes in sequenced biopsies from clear cell RCC patient primary tumors. By investigating lysosome physiology, we also identify VHL-inactivated cells' inability to maintain their lysosomes at the perinuclear localization in response to STF-62247-induced stress and accumulate cytoplasmic inclusion bodies in response to an inefficient lysosomal degradative capacity. Finally, by testing other known lysosomal-disrupting agents (LDAs), we show that these are selectively cytotoxic to cells lacking VHL functions. Our study builds a strong platform that could specifically link genetic clonal ccRCC evolution to lysosomal and trafficking vulnerabilities. Abstract : Inactivation of the von Hippel-Lindau (VHL) gene is the earliest event leading to full blown renal cell carcinoma (RCC). Our study highlights the presence of a lysosome vulnerability specific to VHL-inactivated RCC that could be further exploited.